Estimating opportunity costs of avoided deforestation (REDD): Application of a flexible stepwise approach to the Indonesian pulp sector - Pirard, R. (2008)
Developing countries are expected to contribute to climate change mitigation efforts by reducing deforestation, with financial compensations for associated economic losses. These losses are due to foregone revenues and limited economic development, all of these labeled “opportunity costs”. Their accurate estimation is strategic for at least two reasons: to determine fair compensations, and to prioritize low cost strategies to reduce emissions. However, numerous interpretations of the opportunity cost concept coexist in the literature and in influential reports (e.g. Stern review), with differing estimated values for similar cases. This paper presents a framework to better identify relevant values to the calculations: profits / total national economic value, conservation site / downstream industries. When applied to the pulp sector in Indonesia, the framework yields contrasted opportunity costs. This contrast is due to several factors, including the heterogeneity of the pulp industry, or the availability of non-forested lands to displace activities. These values range from zero to one thousand dollars per hectare per year. To use such a framework would help gain credibility and achieve fairness in negotiations between host countries and other stakeholders, in particular those who fund activities to reduce deforestation